Commissurotomy in treating mitral valvuloplasty narrowing and lung in the treatment of pulmonary stenosis - Vernejoul, Robert (1953)
All surgeons agree in indicating that the mitral valve commissurotomy is the rational and necessary treatment of mitral stenosis and the success of this operation depends on the first and second indications of the results of surgical procedure.